Sosialisasi dan Pembuatan Hidroponik untuk Mendukung Program Penghijauan Lingkungan di Kelurahan Plosokerep, Kecamatan Sananwetan, Kota Blitar - Aldien Ramadhan; Bagus Wahyu Tri Pambudi; Arifiana Nur Hanifah; Dewi Deniaty Sholihah; Nanik Hariyana (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Environmental pollution has become an old problem that often has not been found a solution, one of which is in Plosokerep Village, Sananwetan District, Blitar City. Environmental pollution can cause disruption of the habitat of living things which in turn will affect the population of these living things. Efforts that can be made to reduce environmental pollution, one of which is the reforestation program. One of them can be done with hydroponics. Hydroponics is a farming strategy without using soil, but using water to fulfill plant needs. The polluted environment caused by human activities can make nature unable to return to its unique state. The implementation method used by the KKN 141 UPN